The effect of vitamin D supplementation on pain, quality of life, and nerve conduction studies in women with chronic widespread pain - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
The aim of this study was to investigate the effects of vitamin D supplementation on pain, quality of life, and nerve conduction studies (NCSs) in women with chronic widespread pain (CWP) diagnosed with Vitamin D insufficiency. Thirty-three female participants with CWP and vitamin D insufficiency were included in this open-label trial. They were evaluated by routine NCSs in upper and lower limbs, pain scales, and the Nottingham Health Profile before and 8 weeks after starting vitamin D supplementation therapy. The P-value was adjusted to account for the number of comparisons performed in each assessment. After 8 weeks of treatment, participants reported significantly lower pain scores (P=0.000). The total Nottingham Health Profile score and subscores for pain, emotional reactions, and physical activity domains were significantly lower (0.000 <= P <= 0.008). However, no statistically significant changes in NCSs were detected, except trends toward increases in the amplitudes of left median and ulnar sensory nerve potentials and a decrease in the distal latency of the right median sensory potential (0.01 <= P <= 0.04). Vitamin D supplementation therapy decreased pain and increased quality of life without significantly affecting nerve conduction in patients with CWP. Copyright (C) 2017 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: chronic widespread pain; nerve conduction study; quality of life; treatment; vitamin D insufficiency; D DEFICIENCY; PERIPHERAL NEUROPATHY; HYPOVITAMINOSIS-D; PREVENTION; OUTCOMES